2002
DOI: 10.1262/jrd.48.539
|View full text |Cite
|
Sign up to set email alerts
|

Assay for Penetrability of Frozen-thawed Stallion Spermatozoa into Zona-free Hamster Oocytes.

Abstract: Abstract. In Japan, low availability of equine oocytes makes it very difficult to improve the in vitro fertilization (IVF) system of horses. In this situation, an assay for sperm penetrability into zona-free hamster oocytes could be useful as a simulator of the IVF system. The aim of this study was to clarify the optimum conditions of the pretreatment of frozen-thawed stallion spermatozoa with caffeine and ionophore A23187 (IA) in the penetration assay. Frozen-thawed stallion spermatozoa were washed and then p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Similar results were obtained with equine spermatozoa and bovine or hamster zona-free oocytes, with bovine spermatozoa and equine or porcine zona-free oocytes, and with rat spermatozoa and porcine zona-free oocytes [62][63][64][65]. Sartini and Berger [16] suggest that ligand-receptor conservation mediates the spermatozoa-oolemma binding between porcine and bovine species.…”
Section: Discussionsupporting
confidence: 71%
“…Similar results were obtained with equine spermatozoa and bovine or hamster zona-free oocytes, with bovine spermatozoa and equine or porcine zona-free oocytes, and with rat spermatozoa and porcine zona-free oocytes [62][63][64][65]. Sartini and Berger [16] suggest that ligand-receptor conservation mediates the spermatozoa-oolemma binding between porcine and bovine species.…”
Section: Discussionsupporting
confidence: 71%
“…Caffeine has been shown to induce hyperactivation in bovine sperm and to increase tyrosine phosphorylation and acrosomal exocytosis after induction with lysophosphatidylcholine (LPC) treatment (Marquez & Suarez, ). In stallion sperm, caffeine has been used as a sperm capacitation treatment in IVF studies with 11% (Del Campo, Donoso, Parrish, & Ginther, ) and 4.3% (Morato, Soares, Orero, Mogas, & Miro, ) of fertilized oocytes being reported and up to 49% in hamster zona pellucida‐free oocytes (Matsukawa, Takahashi, & Hanada, ). Caffeine also increased tyrosine phosphorylation levels and acrosomal exocytosis induced by LPC (Hochi, Korosue, Choi, & Oguri, ; Pommer, Rutllant, & Meyers, ).…”
Section: Discussionmentioning
confidence: 99%
“…Sperm pretreatment improves the pronuclear formation rate for ICSI in mice and cattle [40,41]. We previously demonstrated that pretreatment of stallion sperm with ionophore A23187 and caffeine is effective for increasing penetration of zona-free hamster oocytes [21] and the pronuclear formation rate after ICSI [22]. During fertilization, a sperm cytoplastic factor is r eleased an d calcium oscillations are generated in mammalian oocytes [42].…”
Section: Discussionmentioning
confidence: 99%
“…The spermatozoa were then exposed to i o n o p h o r e A 2 3 1 8 7 ( 0 . 1 µ M ; C a l b i o c h e mNovabiochem, La Jolla, CA, USA) for 2 min and resuspended in Hepes-buffered Hanks' medium s u p p l e m e n t e d w i t h 3 m g / m l B S A ( i n i t i a l fractionation by cold alcohol precipitation; Sigma) and 1 mM caffeine (Sigma) for 4-6 h at 37 C [21,22]. Five to ten oocytes with a first polar body were loaded into 1.5 ml microcentrifuge tubes containing 500 µl of M2 medium supplemented with 3 mg/ml BSA and centrifuged at 12,000 g for 3 min to facilitate sperm injection.…”
Section: Icsi Proceduresmentioning
confidence: 99%